Longitudinal assessment of immune responses against Bartonella henselae in experimentally infected cats - Shamsul-Bahri, Nurul Afiqah; Omar, Sharina; Watanabe, Malaika; Mustaffa-Kamal, Farina (Elsevier B.V., 2026)
This study investigated the relationship between innate and adaptive immunity in B. henselae -positive cats by assessing the B. henselae -specific immune markers and bacteremia levels. Five cats were infested with Bartonella -carrying fleas to mimic natural infection, while three healthy cats served as uninfected controls. Blood samples were collected over 12 weeks to evaluate bacterial load from whole blood, TLR-4, TLR-9, IL-10, and TNF-α expression in PBMCs using qPCR, as well as IgM and IgG titers and CD4/CD8 profiles via immunofluorescence and flow cytometry. All experimentally infected cats became bacteremic by Week 1 post-infection (p.i) and remained positive throughout the study, demonstrating successful flea-mediated transmission and persistent infection. Bacterial loads exhibited an undulant pattern with inter-individual variability accompanied by dynamic changes in immune response throughout the study. TNF-α expression was significantly higher in infected cats (p = 0.036) compared to control cats from Week 4 to Week 12 p.i, indicating a delayed pro-inflammatory response. In contrast, no statistically significant differences were observed for TLR-4, TLR-9, or IL-10 expression, although temporal variation was noted. TNF-α and IL-10 expression showed a strong positive correlation, suggesting coordinated regulation of inflammatory and regulatory cytokine responses over time. All infected cats seroconverted by Week 2 p.i, with sustained IgG titers, while altered CD4:CD8 ratios were observed in three of five animals, highlighting heterogeneity in adaptive immune responses. Overall, these findings indicate that B. henselae establishes persistent infection in cats characterized by sustained bacteremia and dynamic, temporally regulated immune responses. This study provides novel insight into the kinetics of innate and adaptive immunity during feline B. henselae infection.